Items tagged with expression expression Tagged Items Feed

Hello people in mapleprimes,

I have an equation called aa in the following.

alias(`δx`=dx, `Δx`=Dx,`Δy`=Dy,`Δz`=Dz):
aa:=Dz=f(x+Dx,y+Dy)-f(x,y);

As for modification of this expression, I ask your favor to teach me.

Then, I want to change this aa to D[1](f)(x+theta__1*Dx,y+Dy)*Dx+D[2](f)(x,y+theta__2*Dy)*Dy.

But, to do so, I have to split aa into the one including -f(x,y+Dy)+f(x,y+Dy) between two terms

of aa.

But, as maple cancels these terms, I can't do so. How can I insert two terms, then

obtain the expression  D[1](f)(x+theta__1*Dx,y+Dy)*Dx+D[2](f)(x,y+theta__2*Dy)*Dy?

 

Thanks in advance.

taro

Hi, I am new to maple, but I think that my question should be simple.

I have a matrix where each element is an expression. I want to compute the matrix for different constant and to save it without crushing the previous matrix. 

If the file that I joined, I have a first part where the constant are defined. In the second part the expression of the matrix is defined. Finally, I compute each matrix with different constant. Each results is called C_p0, C_s0, C_g0. When I called them back, only the last matrix computed remains.

I would like to be able to save each matrix to performed operation on them later.

Thank you. 

 

Forum_Question1.mw

Homogénéisation

 

restart; with(plots); with(DifferentialGeometry); with(LinearAlgebra); with(Physics)

  NULL

Paramètre des matériaux

 

p[p] := [34.68, 34.82]:
NULL

 

NULLNULL

Tenseurs Élémentaires

 

NULL

Tenseur de rigidité

 

V := 1/((1+upsilon[23])*(-2*upsilon[12]*upsilon[21]-upsilon[23]+1)); G[12] := E/(2*(1+upsilon[12])); C[11] := (-upsilon[23]^2+1)*V*E[1]; C[22] := (-upsilon[12]*upsilon[21]+1)*V*E[2]; C[12] := upsilon[21]*(1+upsilon[23])*V*E[2]; C[23] := (upsilon[12]*upsilon[21]+upsilon[23])*V*E[2]; C[44] := (1/2)*(-2*upsilon[12]*upsilon[21]-upsilon[23]+1)*V*E[2]; C[55] := E[6]; C[33] := C[22]; C[13] := C[12]; C[66] := C[55]; C[21] := C[12]; C[32] := C[23]; C[iso] := Matrix(6, 6, {(1, 1) = C[11], (1, 2) = C[12], (1, 3) = C[12], (1, 4) = 0, (1, 5) = 0, (1, 6) = 0, (2, 1) = C[21], (2, 2) = C[22], (2, 3) = C[23], (2, 4) = 0, (2, 5) = 0, (2, 6) = 0, (3, 1) = C[21], (3, 2) = C[32], (3, 3) = C[22], (3, 4) = 0, (3, 5) = 0, (3, 6) = 0, (4, 1) = 0, (4, 2) = 0, (4, 3) = 0, (4, 4) = C[44], (4, 5) = 0, (4, 6) = 0, (5, 1) = 0, (5, 2) = 0, (5, 3) = 0, (5, 4) = 0, (5, 5) = C[66], (5, 6) = 0, (6, 1) = 0, (6, 2) = 0, (6, 3) = 0, (6, 4) = 0, (6, 5) = 0, (6, 6) = C[66]})

Matrice de rigidité

 

upsilon[23] := upsilon[p]:

Matrix([[C[11], C[12], C[12], 0, 0, 0], [C[21], C[22], C[23], 0, 0, 0], [C[21], C[32], C[22], 0, 0, 0], [0, 0, 0, C[44], 0, 0], [0, 0, 0, 0, C[66], 0], [0, 0, 0, 0, 0, C[66]]])

(1.2.1.1.1)

upsilon[23] := upsilon[s]:

Matrix([[C[11], C[12], C[12], 0, 0, 0], [C[21], C[22], C[23], 0, 0, 0], [C[21], C[32], C[22], 0, 0, 0], [0, 0, 0, C[44], 0, 0], [0, 0, 0, 0, C[66], 0], [0, 0, 0, 0, 0, C[66]]])

(1.2.1.1.2)

upsilon[23] := upsilon[g]:

Matrix([[C[11], C[12], C[12], 0, 0, 0], [C[21], C[22], C[23], 0, 0, 0], [C[21], C[32], C[22], 0, 0, 0], [0, 0, 0, C[44], 0, 0], [0, 0, 0, 0, C[66], 0], [0, 0, 0, 0, 0, C[66]]])

(1.2.1.1.3)

``

C[p0];

Matrix([[C[11], C[12], C[12], 0, 0, 0], [C[21], C[22], C[23], 0, 0, 0], [C[21], C[32], C[22], 0, 0, 0], [0, 0, 0, C[44], 0, 0], [0, 0, 0, 0, C[66], 0], [0, 0, 0, 0, 0, C[66]]])

(1)

``

 

Dear Forum, 

 

I am a new Maple user, and its symbolic prowess is really amazing. So we are trying to interface it with a C library. I want to generate some C code through Maple, and am trying the CodeGeneration package. 

But the default conversion of C(a, b) is b = C language equivalent of expression a.

Now this should be fine for most purposes, but the C library that we are working with, "ACADOToolkit" in this case, requires the equations to be formatted in a certain way. So, I need the following equation in C:

 

f << dot(v) == (u-0.2*v*v)/m

 

Now the LHS part of == is to be hard-coded, but we want to generate the equation on the right using maple. Even if I define an equation as 

eq1:= diff(v(t),t)=(u(t)-0.2*v(t)*v(t))/m(t) and then use C(rhs(eq1)), I get the result in the form of cg = u - 0.2 ...., whereas I want this to be assigned to something else, in this case - "f << dot(v)= ".

 

How can I achieve this ?

 

Thanks 

Chintan Pathak 

Research Scholar, 

University of Washington

 

How can I simplify $\sqrt{1−r^2\exp(2i\theta)}$ in Maple. I could do it by hand but I need this type of simplification later for far more complicated expressions.  I allready tried to enter this as a complex number using II, but simplify(...,'symbolic') didn't simplify this expression. Any suggestion?

While performing integration of some expessions I bumped into a strange problem. My expession consists of quite a lot of terms, but here I present the susbset of only 2. If I integrate it as a whole maple does not want to solve it, and leaves it as there was no closed expression to this integral. But if I split this sum and integrate the parts, it all works fine. What is happening here? What do I miss? I used simplify and allvalues but didn't change a thing...

Is there a way to split my terms into list, integrate one by one and they recreate the solution by summing the parts? Its a bit of a workaround, but surely better that doing it manually (I have around 50 terms). I use Maple 2015

Thanks,

Jeremi


Suppose I have a triplet a[5], a[6], a[7]and an expression given as below:

V[5]*a[5]+V[6]*a[6]+V[7]*a[7]+V[2]+V[9]

How I can list all possible forms of above expression for triplet "(a[5], a[6], a[7])->(a[5], a[6], a[7]), (a[5], a[6], 0), (a[5], 0, a[7]), (0, a[6], a[7]), (a[5], 0, 0), (0, a[6], 0 ), (0, 0, a[7]), (0, a[6], 0), (0, 0, 0) "etc


Download triplet.mw

Regards

Hi,

can you please help me with the usage of applyrule? I have the following problem that I cannot isolate. I have a rule that I want to apply, but instead of applying the rule to the expression, the rule seems to be applied to itself. In an isolated worksheet everything is fine:

restart;

rule:=abs(''a''::algebraic)^2=''a''^2;

abs('a'::algebraic)^2 = 'a'^2

(1)

 

myexp:=abs(548.477146186283171377723+radius_motor*q_mot_vec_2(t)-l_wire_0[2])^2

abs(548.477146186283171377723+radius_motor*q_mot_vec_2(t)-l_wire_0[2])^2

(2)

applyrule(rule,myexp);

(548.477146186283171377723+radius_motor*q_mot_vec_2(t)-l_wire_0[2])^2

(3)

rule

abs(a::algebraic)^2 = a^2

(4)

 


Download applyrule.mw

What happens when I try to use this rule in my script is this:

restart;

#read "some_long_script.mpl":

rule:=abs(''a''::algebraic)^2=''a''^2;

abs('a'::algebraic)^2 = 'a'^2

(1)

applyrule(rule,abs(x)^2)

abs(x)^2

(2)

rule

a::algebraic^2 = a^2

(3)

 

>
 

I want to clarify, that the script that is read before applying those rules does not apply a similar rule. Also the variables rule and x were free. Can you please help me to locate the problem?

Thanks!

Honigmelone

Hi all,

I am trying to do some calculation using Maple. I have different expressions containing some power of y. I would like that Maple automatically substitutes y^4 = f(y), in each one of these. So for example, if my expression contains y^5, I want it substituted by y * f(y), and so on. How can I do?

Dear All

I want to use subs command to replace products in expression with entries from matrix. When I use "subs" command it returns same result as original without any substitution. But when I use "algsubs", it works fine, but is complicated to apply if there are large number of substitutions.

Please see followings:

 

M := Matrix([[U[1], U[2], -epsilon*U[1]+U[3], U[4], U[5], U[6]], [U[1], U[2], -epsilon*U[2]+U[3], epsilon*U[1]+U[4], epsilon*U[2]+U[5], U[6]], [e^epsilon*U[1], e^epsilon*U[2], U[3], U[4], U[5], U[6]], [U[1], -epsilon*U[1]+U[2], U[3], U[4], -epsilon*U[4]+U[5], U[6]-epsilon*(U[3]+2*U[5])+epsilon^2*U[4], U[1], e^(-epsilon)*U[2], U[3], e^epsilon*U[4], U[5], e^(-epsilon)*U[6]], [U[1], e^(-epsilon)*U[2], U[3], e^epsilon*U[4], U[5], e^(-epsilon)*U[6]], [epsilon*U[2]+U[1], U[2], U[3], U[4]+epsilon*(U[3]+2*U[5])+epsilon^2*U[6], epsilon*U[6]+U[5], U[6]]])

M := Vector(4, {(1) = ` 6 x 12 `*Matrix, (2) = `Data Type: `*anything, (3) = `Storage: `*rectangular, (4) = `Order: `*Fortran_order})

(1)

M[5, 1]; 1; M[5, 3]

U[1]

 

U[3]

(2)

expand((w*T[5]+z*T[4]+T[6])*(U[1]*a[1]+U[2]*a[2]+U[3]*a[3]+U[4]*a[4]+U[5]*a[5]+U[6]*a[6]))

w*T[5]*U[1]*a[1]+w*T[5]*U[2]*a[2]+w*T[5]*U[3]*a[3]+w*T[5]*U[4]*a[4]+w*T[5]*U[5]*a[5]+w*T[5]*U[6]*a[6]+z*T[4]*U[1]*a[1]+z*T[4]*U[2]*a[2]+z*T[4]*U[3]*a[3]+z*T[4]*U[4]*a[4]+z*T[4]*U[5]*a[5]+z*T[4]*U[6]*a[6]+T[6]*U[1]*a[1]+T[6]*U[2]*a[2]+T[6]*U[3]*a[3]+T[6]*U[4]*a[4]+T[6]*U[5]*a[5]+T[6]*U[6]*a[6]

(3)

subs(T[5]*U[1] = M[5, 1], T[5]*U[2] = M[5, 2], T[5]*U[3] = M[5, 3], w*T[5]*U[1]*a[1]+w*T[5]*U[2]*a[2]+w*T[5]*U[3]*a[3]+w*T[5]*U[4]*a[4]+w*T[5]*U[5]*a[5]+w*T[5]*U[6]*a[6]+z*T[4]*U[1]*a[1]+z*T[4]*U[2]*a[2]+z*T[4]*U[3]*a[3]+z*T[4]*U[4]*a[4]+z*T[4]*U[5]*a[5]+z*T[4]*U[6]*a[6]+T[6]*U[1]*a[1]+T[6]*U[2]*a[2]+T[6]*U[3]*a[3]+T[6]*U[4]*a[4]+T[6]*U[5]*a[5]+T[6]*U[6]*a[6])

w*T[5]*U[1]*a[1]+w*T[5]*U[2]*a[2]+w*T[5]*U[3]*a[3]+w*T[5]*U[4]*a[4]+w*T[5]*U[5]*a[5]+w*T[5]*U[6]*a[6]+z*T[4]*U[1]*a[1]+z*T[4]*U[2]*a[2]+z*T[4]*U[3]*a[3]+z*T[4]*U[4]*a[4]+z*T[4]*U[5]*a[5]+z*T[4]*U[6]*a[6]+T[6]*U[1]*a[1]+T[6]*U[2]*a[2]+T[6]*U[3]*a[3]+T[6]*U[4]*a[4]+T[6]*U[5]*a[5]+T[6]*U[6]*a[6]

(4)

Why this command subs in not replacing  products  T[5]*U[1], T[5]*U[2], T[5]*U[3] from matrix (1)NULL?????

algsubs(T[5]*U[1] = M[5, 1], w*T[5]*U[1]*a[1]+w*T[5]*U[2]*a[2]+w*T[5]*U[3]*a[3]+w*T[5]*U[4]*a[4]+w*T[5]*U[5]*a[5]+w*T[5]*U[6]*a[6]+z*T[4]*U[1]*a[1]+z*T[4]*U[2]*a[2]+z*T[4]*U[3]*a[3]+z*T[4]*U[4]*a[4]+z*T[4]*U[5]*a[5]+z*T[4]*U[6]*a[6]+T[6]*U[1]*a[1]+T[6]*U[2]*a[2]+T[6]*U[3]*a[3]+T[6]*U[4]*a[4]+T[6]*U[5]*a[5]+T[6]*U[6]*a[6])

z*T[4]*U[2]*a[2]+z*T[4]*U[3]*a[3]+z*T[4]*U[4]*a[4]+z*T[4]*U[5]*a[5]+z*T[4]*U[6]*a[6]+T[6]*U[2]*a[2]+T[6]*U[3]*a[3]+T[6]*U[4]*a[4]+T[6]*U[5]*a[5]+T[6]*U[6]*a[6]+(w*U[2]*a[2]+w*U[3]*a[3]+w*U[4]*a[4]+w*U[5]*a[5]+w*U[6]*a[6])*T[5]+(z*T[4]*a[1]+w*a[1]+T[6]*a[1])*U[1]

(5)

It worked !!!! But If I try "algsubs" like :

algsubs(T[5]*U[1] = M[5, 1], T[5]*U[2] = M[5, 2], T[5]*U[3] = M[5, 3], w*T[5]*U[1]*a[1]+w*T[5]*U[2]*a[2]+w*T[5]*U[3]*a[3]+w*T[5]*U[4]*a[4]+w*T[5]*U[5]*a[5]+w*T[5]*U[6]*a[6]+z*T[4]*U[1]*a[1]+z*T[4]*U[2]*a[2]+z*T[4]*U[3]*a[3]+z*T[4]*U[4]*a[4]+z*T[4]*U[5]*a[5]+z*T[4]*U[6]*a[6]+T[6]*U[1]*a[1]+T[6]*U[2]*a[2]+T[6]*U[3]*a[3]+T[6]*U[4]*a[4]+T[6]*U[5]*a[5]+T[6]*U[6]*a[6])

Error, invalid input: algsubs expects its 3rd argument, x, to be of type {name, function, list({name, function}), set({name, function})}, but received T[5]*U[3] = U[3]

 

See it is giving error !!! but still I can use "algsubs" as follow:

 

expand(algsubs(T[6]*U[6] = M[6, 6], expand(algsubs(T[6]*U[5] = M[6, 5], expand(algsubs(T[6]*U[4] = M[6, 4], expand(algsubs(T[6]*U[3] = M[6, 3], expand(algsubs(T[6]*U[2] = M[6, 2], expand(algsubs(T[6]*U[1] = M[6, 1], expand(algsubs(T[5]*U[6] = M[5, 6], expand(algsubs(T[5]*U[5] = M[5, 5], expand(algsubs(T[5]*U[4] = M[5, 4], expand(algsubs(T[5]*U[3] = M[5, 3], expand(algsubs(T[5]*U[2] = M[5, 2], expand(algsubs(T[5]*U[1] = M[5, 1], expand(algsubs(T[4]*U[6] = M[4, 6], expand(algsubs(T[4]*U[5] = M[4, 5], expand(algsubs(T[4]*U[4] = M[4, 4], expand(algsubs(T[4]*U[3] = M[4, 3], expand(algsubs(T[4]*U[2] = M[4, 2], expand(algsubs(T[4]*U[1] = M[4, 1], expand(algsubs(T[3]*U[6] = M[3, 6], expand(algsubs(T[3]*U[5] = M[3, 5], expand(algsubs(T[3]*U[4] = M[3, 4], expand(algsubs(T[3]*U[3] = M[3, 3], expand(algsubs(T[3]*U[2] = M[3, 2], expand(algsubs(T[3]*U[1] = M[3, 1], expand(algsubs(T[2]*U[6] = M[2, 6], expand(algsubs(T[2]*U[5] = M[2, 5], expand(algsubs(T[2]*U[4] = M[2, 4], expand(algsubs(T[2]*U[3] = M[2, 3], expand(algsubs(T[2]*U[3] = M[2, 3], expand(algsubs(T[2]*U[2] = M[2, 2], expand(algsubs(T[2]*U[1] = M[2, 1], expand(algsubs(T[1]*U[6] = M[1, 6], expand(algsubs(T[1]*U[5] = M[1, 5], expand(algsubs(T[1]*U[4] = M[1, 4], expand(algsubs(T[1]*U[3] = M[1, 3], expand(algsubs(T[1]*U[2] = M[1, 2], expand(algsubs(T[1]*U[1] = M[1, 1], w*T[5]*U[1]*a[1]+w*T[5]*U[2]*a[2]+w*T[5]*U[3]*a[3]+w*T[5]*U[4]*a[4]+w*T[5]*U[5]*a[5]+w*T[5]*U[6]*a[6]+z*T[4]*U[1]*a[1]+z*T[4]*U[2]*a[2]+z*T[4]*U[3]*a[3]+z*T[4]*U[4]*a[4]+z*T[4]*U[5]*a[5]+z*T[4]*U[6]*a[6]+T[6]*U[1]*a[1]+T[6]*U[2]*a[2]+T[6]*U[3]*a[3]+T[6]*U[4]*a[4]+T[6]*U[5]*a[5]+T[6]*U[6]*a[6]))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))

a[5]*epsilon*U[6]+a[1]*epsilon*U[2]+U[6]*a[6]+U[2]*a[2]+U[3]*a[3]+U[4]*a[4]+U[5]*a[5]+z*a[1]*U[1]+epsilon^2*U[6]*a[4]+epsilon*U[3]*a[4]+2*epsilon*U[5]*a[4]+U[6]*w*a[6]/e^epsilon+U[4]*e^epsilon*w*a[4]+w*a[1]*U[1]+U[2]*w*a[2]/e^epsilon+epsilon^2*z*U[4]*a[6]-epsilon*z*U[3]*a[6]-2*epsilon*z*U[5]*a[6]+w*U[3]*a[3]+w*U[5]*a[5]-z*a[5]*epsilon*U[4]-z*a[2]*epsilon*U[1]+z*U[2]*a[2]+z*U[3]*a[3]+z*U[4]*a[4]+z*U[5]*a[5]+z*U[6]*a[6]+a[1]*U[1]

(6)

But this procedure is complex, I want to use "subs" only. I know it complexity of terms in (3) might me creating problem.

collect(a[5]*epsilon*U[6]+a[1]*epsilon*U[2]+U[6]*a[6]+U[2]*a[2]+U[3]*a[3]+U[4]*a[4]+U[5]*a[5]+z*a[1]*U[1]+epsilon^2*U[6]*a[4]+epsilon*U[3]*a[4]+2*epsilon*U[5]*a[4]+U[6]*w*a[6]/e^epsilon+U[4]*e^epsilon*w*a[4]+w*a[1]*U[1]+U[2]*w*a[2]/e^epsilon+epsilon^2*z*U[4]*a[6]-epsilon*z*U[3]*a[6]-2*epsilon*z*U[5]*a[6]+w*U[3]*a[3]+w*U[5]*a[5]-z*a[5]*epsilon*U[4]-z*a[2]*epsilon*U[1]+z*U[2]*a[2]+z*U[3]*a[3]+z*U[4]*a[4]+z*U[5]*a[5]+z*U[6]*a[6]+a[1]*U[1], [U[1], U[2], U[3], U[4], U[5], U[6]])

(-epsilon*z*a[2]+w*a[1]+z*a[1]+a[1])*U[1]+(a[1]*epsilon+a[2]+w*a[2]/e^epsilon+z*a[2])*U[2]+(-epsilon*z*a[6]+epsilon*a[4]+w*a[3]+z*a[3]+a[3])*U[3]+(epsilon^2*z*a[6]+e^epsilon*w*a[4]-z*a[5]*epsilon+z*a[4]+a[4])*U[4]+(-2*epsilon*z*a[6]+2*epsilon*a[4]+w*a[5]+z*a[5]+a[5])*U[5]+(a[5]*epsilon+a[6]+epsilon^2*a[4]+w*a[6]/e^epsilon+z*a[6])*U[6]

(7)

``

 

Download Subs_not_giving_result.mwSubs_not_giving_result.mw

Regards

 

2*t*exp(t) + 2*t

would like to apply op recurively 

and output list

[2,t,exp(t),2,t]

Hi all!

as shown below, how can get a result without 'R':

p_com(z,t):=Re(exp(I*omega*t-I*k*(lambda[r]+I*lambda[i])*z)) assuming omega::real,t::real,k::real,lambda[r]::real,lambda[i]::real,z::real

Thanks very much!

 

Hi Guys, 

I'm trying to find stationary points of a numeric function. Any help would be appreciated. 

Assume I have a numeric function g(x). I'm attempting the following:

deriv:=(x)->fdiff(g(t),t=x); (I can't use the D operator as it doesn't like g(x))

Now deriv(x) <- Can be computed and computes the value quickly and easily. However plot and other functions require algebraic functions. I can plot this (with difficulty) via the following

plot(deriv,-10..10) <- This avoids converting to algebraic function and runs as a procedure. 

I can't use convert(deriv,algebraic) as it fails. 

I want to use the Student[NumericalAnalysis]Roots command, but it requires an algebraic function and I can't use the procedure trick which I did in the plot command. 

Does anyone know a better way of doing this? or is there a way I can write the numerical differivative as an algebraic function. (I've tried fsolve <- But this guy doesn't give me the correct answers generally). 

Thanks guys. 

 

 

 

Dear All

How can we collect coefficient wrt certain differential ration in an expression?

See for detail:


with(PDEtools):

u := a[0]+a[1]*(diff(phi(xi), xi))/phi(xi)

a[0]+a[1]*(diff(phi(xi), xi))/phi(xi)

(1)

-k*(diff(u, `$`(xi, 2)))+alpha*(diff(u, `$`(xi, 3)))

-k*(a[1]*(diff(diff(diff(phi(xi), xi), xi), xi))/phi(xi)-3*a[1]*(diff(diff(phi(xi), xi), xi))*(diff(phi(xi), xi))/phi(xi)^2+2*a[1]*(diff(phi(xi), xi))^3/phi(xi)^3)+alpha*(a[1]*(diff(diff(diff(diff(phi(xi), xi), xi), xi), xi))/phi(xi)-4*a[1]*(diff(diff(diff(phi(xi), xi), xi), xi))*(diff(phi(xi), xi))/phi(xi)^2+12*a[1]*(diff(diff(phi(xi), xi), xi))*(diff(phi(xi), xi))^2/phi(xi)^3-3*a[1]*(diff(diff(phi(xi), xi), xi))^2/phi(xi)^2-6*a[1]*(diff(phi(xi), xi))^4/phi(xi)^4)

(2)

expand(dsubs(diff(phi(xi), `$`(xi, 2)) = -lambda*(diff(phi(xi), xi))-mu*phi(xi), -k*(a[1]*(diff(diff(diff(phi(xi), xi), xi), xi))/phi(xi)-3*a[1]*(diff(diff(phi(xi), xi), xi))*(diff(phi(xi), xi))/phi(xi)^2+2*a[1]*(diff(phi(xi), xi))^3/phi(xi)^3)+alpha*(a[1]*(diff(diff(diff(diff(phi(xi), xi), xi), xi), xi))/phi(xi)-4*a[1]*(diff(diff(diff(phi(xi), xi), xi), xi))*(diff(phi(xi), xi))/phi(xi)^2+12*a[1]*(diff(diff(phi(xi), xi), xi))*(diff(phi(xi), xi))^2/phi(xi)^3-3*a[1]*(diff(diff(phi(xi), xi), xi))^2/phi(xi)^2-6*a[1]*(diff(phi(xi), xi))^4/phi(xi)^4)))

-a[1]*(diff(phi(xi), xi))*alpha*lambda^3/phi(xi)-a[1]*alpha*lambda^2*mu-7*a[1]*(diff(phi(xi), xi))^2*alpha*lambda^2/phi(xi)^2-8*a[1]*(diff(phi(xi), xi))*alpha*lambda*mu/phi(xi)-a[1]*(diff(phi(xi), xi))*k*lambda^2/phi(xi)-2*a[1]*alpha*mu^2-a[1]*k*lambda*mu-12*a[1]*(diff(phi(xi), xi))^3*alpha*lambda/phi(xi)^3-8*a[1]*(diff(phi(xi), xi))^2*alpha*mu/phi(xi)^2-3*a[1]*(diff(phi(xi), xi))^2*k*lambda/phi(xi)^2-2*a[1]*(diff(phi(xi), xi))*k*mu/phi(xi)-6*a[1]*(diff(phi(xi), xi))^4*alpha/phi(xi)^4-2*a[1]*(diff(phi(xi), xi))^3*k/phi(xi)^3

(3)

How ca extract coefficients of fraction (diff(phi(xi), xi))/phi(xi) in (3) ????


Download Coefficients_of_Fractions.mw

Regards

I am wondering why Maple does this.

> f:=x^2
> f(3)
output: x(3)^2

I understand the difference between an expression and a function. If f is an expression, shouldn't it ouput  x^2(3). Why is the output x(3)^2?

When I enter f*3 or f*(3) then I get the correct expression.

Here is a screenshot. http://prntscr.com/a7u9hm

Here is image inserted with a slightly different function

 

Also while I am here, what exactly does g(x):= x^2 do? when i enter g(3) I get g(3) back.

g(x) is neither a function nor an expression.

screenshot http://prntscr.com/a7ua75



 I am haunted by an equation which I could simplify it with hand and it equals to −i (complexe number). But, I don't know how to use maplesoft to simplify it. The equation takes the form of:

 

-Omega*a*sqrt(2)*sqrt(-Omega^2*a^2-2*k*m+sqrt(Omega^2*a^2*(Omega^2*a^2+4*k*m)))/(-Omega^2*a^2+sqrt(Omega^2*a^2*(Omega^2*a^2+4*k*m)))



I could simplify this equation with hand calculation and it equals to -i (the complexe number). I'am sorry for not clarifying that the a, k, Ω and m are positive variables.

Thank you in advance for taking a look.
1 2 3 4 5 6 7 Last Page 1 of 10